PENGARUH DIFERENSIASI PRODUK TERHADAP PENIGKATAN VOLUME PENJUALAN PADA UD. LIS TELUKDALAM KAB. NISEL - Bali, Santrianis (LPPM Universitas Nias Raya, 2024)
The problem with this invention is the lack of product differentiation based on shape. The direction of this discovery is knowing the influence of product differentiation on increasing sales at UD. LIS Telda District. Nisel. The types used in this discovery are as follows: Quantitate. The subjects in this research were UD Lis Telukdalam with 36 consumers. The result is that there is an influence of product differentiation on increasing sales as evidenced by the high value for the product differentiation variable (X) according to the researchers: There is a need to adjust strategies in dividing community groups in purchasing goods to increase sales, which occurs at UD. LIS Teldam District. Nisel. Good for the time and in the future and have positive hopes for increasing sales so that more products can be sold to support sales levels.